1998
DOI: 10.1080/001401398186586
|View full text |Cite
|
Sign up to set email alerts
|

Preferred position of visual displays relative to the eyes: a field study of visual strain and individual differences

Abstract: At office workplaces equipped with visual display units (VDU) that were adjustable to various positions relative to the eyes short and long viewing distances from the eyes to the screen were imposed (mean value of about 63 and 92 cm) at two levels of screen height so that the visual target was either at eye level or 18 cm below, on the average. The change from far to near viewing distance produced a larger increase in eyestrain when the VDUs were at eye level. High screens resulted in greater eyestrain than lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
90
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(104 citation statements)
references
References 23 publications
8
90
0
2
Order By: Relevance
“…It was found in a study that the change from a greater to a lesser viewing distance produced a larger increase in the eyestrain when the VDTs were at eye level [13]. Another study showed that the asthenopia was less in the subjects whose viewing distance was more than 30 cm (12 inches) and that it was the highest when the viewing distance was less than 30 cm (12 inches), which was statistically significant [3].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…It was found in a study that the change from a greater to a lesser viewing distance produced a larger increase in the eyestrain when the VDTs were at eye level [13]. Another study showed that the asthenopia was less in the subjects whose viewing distance was more than 30 cm (12 inches) and that it was the highest when the viewing distance was less than 30 cm (12 inches), which was statistically significant [3].…”
Section: Discussionmentioning
confidence: 97%
“…Studies have reported increased odds ratios for certain eye discomfort symptoms when the computer operators kept the terminal at about the eye level rather than below the eye level [10]. Studies have found that high screens result in greater eyestrain than the low screens [13].…”
Section: Discussionmentioning
confidence: 99%
“…Chair design has the potential to influence viewing angle and distance. Recommended optimum viewing ranges vary from 50 to 100 cm (Taptagaporn and Saito, 1993;Taptagaporn et al, 1995;Jaschinski et al, 1998). Recent studies suggest the optimum distance is linked to the user's vision system and is best chosen by the worker (Jainta and Jaschinski, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Poor workstation design coupled with high workload, postural demands, and job demands have been found to contribute to shoulder, neck, back, and wrist-hand discomfort or pain [2][3][4] . Furthermore, improper illumination and glare, work demands, computer screen design, and task characteristics have been found to contribute to visual discomfort 5,6) . Since computerized jobs are more sedentary, and require more cognitive processing and mental attention, many jobs that require heavy daily computer use have been found to be stressful 7,8) .…”
Section: Introductionmentioning
confidence: 99%